Assessment of term newborn care recommendations in the curricula at a baccalaureate-level nursing school and tertiary public maternity hospital in western Kenya: an analysis of secondary data from a rapid, focused, ethnographic assessment - Davika Reid, PhD; Dinah Chelagat, PhD; Lauren Gulbas, PhD; Timothy Mercer, MD; Lorraine Walker, PhD; Julie Zuniga, PhD; Alexandra Garcia, PhD (The Lancet Global Health, 2020)
Background: To address high neonatal mortality (from birth to 28 days of life), baccalaureate-level nursing school and continuing education curricula in western Kenya include content on most common causes of death in the first week of life and the prevention and treatment of complications such as low birthweight, respiratory distress, and sepsis. Yet these topics do not address early-to-late postnatal mortality in well-appearing, term newborns discharged more than 24 h after delivery. In this study, we assessed curricula at a baccalaureate-level university nursing school and a tertiary hospital in western Kenya for content on home care of term newborns. Methods: We analysed secondary data using a rapid, focused ethnographic study of newborn care recommendations provided by nurse-midwives on the postnatal ward of a tertiary, publicly funded referral hospital and baccalaureate-level nursing school in western Kenya. Participants were recruited via purposive stratified judgment sampling. We conducted anonymous, semi-structured, open-ended interviews with nursing faculty, administrators, bedside staff, and one obstetric resident physician. Data were analysed using thematic analysis. Findings: Between Nov 17 and Dec 17, 2018, we conducted 24 interviews and completed 240 h of participant observation, reviewed 34 relevant documents (obstetric and paediatric syllabi and ward-specific continuing education logs), and took 268 pages of fieldnotes. The nursing school curriculum provided less than 6 h of didactic instruction on well-newborn care recommendations, divided between obstetric and paediatric courses. In the hospital, 80% of the monthly continuing education topics focused on maternal health and 20% focused on care of the sick newborn, despite only well-appearing newborns being present on the ward. Workforce capacity constraints limited clinical instruction about home care recommendations and contributed to early discharge of the well-appearing newborn before the recommended period of observation after birth. Interpretation: The teaching of term newborn topics within the obstetric and paediatric nursing curriculum and limited hospital continuing education programme may be disadvantageous to well-appearing newborns as the newborns' evolving postnatal health needs may be overshadowed by concern for mothers and sick newborns. Our findings suggest a need for increased coverage of postnatal newborn health topics in nursing curricula within the study settings, for larger studies to assess content endorsed by the Nursing Council of Kenya, and increased vigilance of newborn health after discharge. Additional coverage of term newborn health topics may increase use of evidence-based care recommendations to prevent complications during ongoing newborn physiological transition, encourage partnership with caregivers to promote newborn health throughout the full postnatal period, and decrease neonatal mortality. Study strengths include an adequate sample and rich narratives for thematic saturation; limitations include secondary analysis and possible recall bias of participants. Funding: RWJF Future of Nursing Scholars; University of Texas at Austin School of Nursing